فاعلية التكامل بين إنموذجي دورة التعلم الثلاثية وخرائط المفاهيم في تحصيل مادة الرياضيات لدى طلاب الصف الاول المتوسط - جاسم السراي ميعاد; ناصر حفاتي جهاد (Al-Adab Journal, 2018)
The objective of the current research to identify the Efficiency Integrating Between The Models of Learning Cycle and Concepts Maps for Achievement in Mathematics of the Students for First –intermidiat. The sample consisted of (65) Students from the 1st grade students of the new rising for boys of the directorate of education Baghdad al Rasafa 3 , Rose (33) students in the experimental Group, (32) students in the group Control The collection by test (40) clause (34) clause of the kind of subjective-and (6) paragraphs of article items , It was the verification of the truthfulness and sincerity of virtual test- labs test content and the calculation of the flat ,with the method of split half bringing using the equation of Gutman (0.861), Using the appropriate statistical methods the results above the students of the Experimental Group who studied the efficiency integrating between the models of learning cycle and concepts maps session on students who studied the Control group in the usual way in the Achievement Test, in the light of these results reached a number of Conclusions and Recommendations and Proposals.